The protective effect of farm animal exposure on childhood allergy is modified by NPSR1 polymorphisms. Issue 3 (19th February 2008) - Bruce, S; Nyberg, F; Melén, E; James, A; Pulkkinen, V; Orsmark-Pietras, C; Bergström, A; Dahlén, B; Wickman, M; von Mutius, E; Doekes, G; Lauener, R; et al.
Abstract : Background: Little is known about the asthma candidate gene neuropeptide S receptor 1 ( NPSR1 ) in relation to environmental exposures, but recent evidences suggest its role as an effect modifier. Objectives: To explore the interaction between NPSR1 polymorphisms and environmental exposures related to farming lifestyle and to study the in vitro effects of lipopolysaccharide (LPS) stimulation on NPSR1 expression levels. Methods: We studied 3113 children from PARSIFAL, a European cross-sectional study on environmental/lifestyle factors and childhood allergy, partly focused on children brought up on a farm. Information on exposures and outcomes was primarily obtained from parental questionnaires. Seven tagging polymorphisms were analysed in a conserved haplotype block of NPSR1 . Multivariate logistic regression was used to evaluate a multiplicative model of interaction. NPSR1 protein and messenger RNA (mRNA) levels in monocytes were measured after LPS stimulation by fluorescence activated cell sorting (FACS) and quantitative real-time polymerase chain reaction (PCR). Results: A strong interaction was seen between current regular contact to farm animals and several NPSR1 polymorphisms, particularly rs323922 and rs324377 (p<0.005), with respect to allergic symptoms. Considering the timing of initiation of such current regular farm animal contact, significant interactions with these and two additional polymorphisms (SNP546333, rs740347) were revealed. In response to LPS, NPSR1-A protein levels in monocytes were upregulated (p = 0.002), as were NPSR1-A mRNA levels (p = 0.02). Conclusions: The effect of farm animal contact on the development of allergic symptoms in children is modified by NPSR1 genetic background.